Effect of curcumin and 4-n-propil curcumin on glutation s-transferase activity in rat liver - Kusumawati, Fitriyah; Martono, Sudibyo; ., Supardjan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Curcumin, a plant phenol in rhizome Curcuma longa L. has been reported to be a potent inhibitor of glutathione S-transferase (GST) in rat liver with in vitro with substrate 1,2-dikloro-4-nitrobenzen (DCNB). By using DCNB, a specific substrate for GST mu, This work was aimed to know whether curcumin derivatives: 4-n-propyl curcumin can also inhibit GST activity in vitro.Glutathione activity can be measured by conjugating GSH and DCNB catalized with GST. The product can be measured spectrofotometrically. Curcumin and its derivatives decreased GST activities with IC50 values 6,86 μM for curcumin and 8,41 μM for 4-n-propyl curcumin. This means that 4-n-propyl curcumin has a weaker inhibition potency than curcumin.Curcumin (consentration 10μM) inhibited GST activity by mixed with the Ki dan Ki’ values 2,77 μM dan 7,33 μM, whereas 4-n-propyl curcumin (consentration 10μM) inhibited GST activity by competitive with the Ki values 6,28 μM.Key words : Curcumin, 4-n-propyl curcumin, glutathione S-transferase, 1,2-dikloro-4-nitrobenzen.